Volume brings value. Issue 4 (19th October 2018) - Gogas, Bill D.; Chen, Shao‐Liang
Key Points: What the article teaches The article highlights the competency of high volume operators across institutions that despite moving to lower volume centers retain their good clinical outcomes. How it will impact practice Although current U.S. based guidelines suggest a volume of at least 50 PCIs annually for operators to retain clinical competency this estimate may be a poor index to guarantee optimal clinical outcomes. What new research/study would help answer the question New studies using a comprehensive definition to define an experienced operator from the Asia‐Pacific—a geographic area that has pioneered in complex coronary interventions—need to elute on the threshold of adequate clinical competency stratified according to clinical complexity.